ESTERIFICATION OF FREE FATTY ACIDS WITH METHANOL TO BIODIESEL USING HETEROGENEOUS ACID CATALYSTS - Caetano, C (2012)
The esterification of palmitic acid with methanol was studied using poly(vinyl alcohol) crosslinked with sulfosuccinic acid (SSA) and polystyrene crosslinked with di-vinylbenzene with sulfonic acid groups, as catalysts, at 60ºC. It was observed that the PVA matrixes with sulfonic acid groups were more actives than the polystyrene ones. An equilibrium conversion of about 90% was achieved after 6 hours, with the most active polymeric matrix (PVA_SSA40). The PVA_SSA40 was also used as catalyst in the esterification of oleic and stearic acid.